Ovulation Induction Techniques in Polycystic Ovary Syndrome - Systematic Review - Daria Michałka; Natalie Papachristoforou; Natalia Tekiela; Zuzanna Gałuszka; Monika Makar; Tomasz Bartuś; Emilia Bąk; Justyna Głowacka; Aleksandra Kocjan; Radosław Chmiel (Quality in Sport, 2025)
Introduction & Purpose of Research: Polycystic Ovary Syndrome (PCOS) is a common hormonal disorder affecting women of reproductive age. Given the high prevalence of PCOS and its impact on infertility, this research explores strategies to stimulate ovulation and improve pregnancy outcomes. To address this issue comprehensively, we specifically selected six main treatment methods: lifestyle changes, clomiphene citrate, antidiabetic drugs, gonadotropin analogues, aromatase inhibitors, and surgical approaches. Our aim was to review various studies, including meta-analyses and comparisons of methods from published texts, to gain valuable insights into the topic.